Self-concept, family relationship, deviant peer socialization and externalizing behavior problems among at risk students in Selangor, Malaysia - Zakaria, Patonah (2018)
The aim of this study was to determine the relationships between self-concept, family relationship, deviant peer socialization and externalizing behavior problem among adolescents with the disciplinary problem in Selangor. This study used a quantitative approach and survey technique by applying descriptive and inferential analysis. Besides that, the study used mediator analysis to measure the mediator effect of selfconcept towards the relationship between independent variables and the dependent variables. A total of 400 adolescents aged 13 to 18 years old from eight secondary schools in the state of Selangor were selected for this study. A survey with the selfadministered questionnaire was employed to collecting the data and multi-stage cluster sampling were used for the selection of the respondents. The respondents were chosen among students with disciplinary problem assist by teachers. Data were utilized from a set of questionnaire which are consists of social demographic background, family relationship (Family Relationship Characteristics scale), deviant peer socialization (Peer Deviancy Scale), self-concept (Individual Protective Factors Index Questionnaire), externalizing behavior (Aggression Scale and Problem Behavior Frequency Scale). Findings revealed that majority of respondents show the moderate level of self-concept, family relationship, and externalizing behaviors, meanwhile for deviant peer socialization majority of respondents showed that they have low deviant peers. The results of T-test showed that there were significant differences in family beliefs, family structure and deviant peers socialization based on gender and age. There were significant differences in aggressive and delinquent behavior based on gender, while self-concept have significant differences in terms of age. Findings also indicated that family relationship (family cohesion and family structure), self-concept, deviant peer socialization have a significant relationship with the aggressive behavior. Finding also found that family structure and deviant peer socialization shows a significant relationship with the delinquency behavior. The multiple regression analysis showed that predictor variables, namely sex, deviant peer socialization, family structure and self-concept have significantly predict aggressive behavior [R2 = 0.17, F (6,701.71) = 17.41, p<0.05] while, significant predictors of delinquency behavior was sex and deviant peer socialization [R2 = 0.47, F (2,363.52) =119.52, p<0.001]. The results of regression analysis using stepwise method show that the socialization of deviant peers was the most important predictor in predicting aggressive behavior, followed by family structure, self-concept, and sex. Regression analysis also shows that the deviant peer socialization was the most important predictor in predicting delinquent behavior, followed by sex. Mediator test indicated that self-concept is the mediator of the relationship between adolescent’s family relationship quality and externalizing behavior. The results of this study have important implications for those involved in school and adolescents systems. Awareness about the influence and impact of self concept, the family relationship and deviant peer socialization to those involved in adolescents’ development system is very important. This knowledge will contribute to the development of more positive externalizing behavior among adolescents, for example in drafting any related program, the self-concept must takes into consideration to ensure the enhancement of psychosocial well-being of adolescents will be achieve.